2021
DOI: 10.1136/bmjgh-2021-006874
|View full text |Cite
|
Sign up to set email alerts
|

Mapping global trends in vaccine sales before and during the first wave of the COVID-19 pandemic: a cross-sectional time-series analysis

Abstract: BackgroundWhile the COVID-19 pandemic may have substantially hindered the provision of routine immunisation services worldwide, we have little data on the impact of the pandemic on vaccine supply chains.MethodsWe used time-series analysis to examine global trends in vaccine sales for a total of 34 vaccines and combination vaccines using data from the IQVIA MIDAS Database between August 2014 and August 2020 across 84 countries. We grouped countries into three income-level categories, and we modelled the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Data are internally validated each year through a standardized quality assurance program which validates sales data for each product against alternate sources by comparing estimated sales volumes against clients' actual sales volumes. 17 , 18 Medication sales data is projected to represent national pharmacy sales across all jurisdictions, regardless of payer. 17 Among the 66 countries in the current analysis, MIDAS captured an average of 89.5% of national sales.…”
Section: Methodsmentioning
confidence: 99%
“…Data are internally validated each year through a standardized quality assurance program which validates sales data for each product against alternate sources by comparing estimated sales volumes against clients' actual sales volumes. 17 , 18 Medication sales data is projected to represent national pharmacy sales across all jurisdictions, regardless of payer. 17 Among the 66 countries in the current analysis, MIDAS captured an average of 89.5% of national sales.…”
Section: Methodsmentioning
confidence: 99%
“…Many companies manufacturing the vaccine have benefited from the sales. An analysis carried out by Zeitouny et al revealed that the demand for vaccines was significantly higher in low and middle-income states compared to high-income states during the first wave of the pandemic ( 8 ). These factors imply that the enhanced demand for vaccines increased the need for more enterprises to manufacture the product.…”
Section: Discussionmentioning
confidence: 99%
“…13–15 IQVIA-MIDAS covers 89.5% of all community-based and hospital-based pharmacy purchases of registered products. 16–18 Further database validation is included in online supplemental appendix B .…”
Section: Methodsmentioning
confidence: 99%